Gender-based technical efficiency analysis of smallholder palm oil plantations in North Sumatra, Indonesia - JONES SIMATUPANG; M. AKBAR SIREGAR; MHD. BUHARI SIBUEA (Smujo International, 2025)
Abstract. Simatupang J, Siregar MA, Sibuea MB. 2025. Gender-based technical efficiency analysis of smallholder palm oil plantations in North Sumatra, Indonesia. Asian J Agric 9: 766-776. The productivity of smallholder palm oil plantations, managed by both male and female farmers, has recently been low due to inefficient allocation of inputs. Previous efficiency literature in Indonesia has not focused on examining differences in technical efficiency between the two genders of smallholder household heads and has used parametric methods. This study examines which oil palm farming is more efficient based on gender and the determinants of technical efficiency of smallholder farmers in North Sumatra, Indonesia. North Sumatra is a key region for palm oil production in Indonesia, and understanding the efficiency of smallholder farmers in this region can provide valuable insights for the entire industry. Input-output and socio-economic data on palm oil production activities in 2023 were collected from 273 male smallholders and 177 female smallholders. We employed Data Envelopment Analysis (DEA) to assess technical efficiency. We employed the Tobit model to examine the influence of socio-economic factors on the technical efficiency of smallholder farmers in the study area. We found that female smallholders are more efficient than male smallholders. However, inefficient female smallholders must reduce inputs to make their farming efficient. This study highlights the crucial role of access to credit, ICT, and farmer groups in technical efficiency. Government policies are expected to lower interest rates, simplify credit application requirements, develop extensive ICT infrastructure in smallholder plantations, and assist with access to capital and information dissemination within farmer groups. Government intervention is expected to improve the technical efficiency and economic sustainability of smallholder oil palm plantations in North Sumatra.